2020
DOI: 10.3389/fnagi.2020.588872
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Neuropsychiatric Manifestations of COVID-19 and Effects on Elderly Individuals With Dementia

Abstract: The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread worldwide and has had unprecedented effects in healthcare systems, economies and society. COVID-19 clinical presentation primarily affects the respiratory system causing bilateral pneumonia, but it is increasingly being recognized as a systemic disease, with neurologic manifestations reported in patients with mild symptoms but, most frequently, in those in a severe condition. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 97 publications
(126 reference statements)
2
106
0
25
Order By: Relevance
“…COVID-19 was initially considered almost exclusively a respiratory syndrome, but increasing evidence indicates that SARS-CoV-2 infection also affects other body districts and functions [ 1 ]. More specifically, studies have shown that SARS-CoV-2 is capable of invading the central nervous system (CNS) and causing neurological symptoms [ 2 , 3 , 4 , 5 , 6 ]. Indeed, many coronaviruses are capable of altering the structure and function of the nervous system [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 was initially considered almost exclusively a respiratory syndrome, but increasing evidence indicates that SARS-CoV-2 infection also affects other body districts and functions [ 1 ]. More specifically, studies have shown that SARS-CoV-2 is capable of invading the central nervous system (CNS) and causing neurological symptoms [ 2 , 3 , 4 , 5 , 6 ]. Indeed, many coronaviruses are capable of altering the structure and function of the nervous system [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding to ACE2 receptors also leads to increased blood pressure that increases the chances of cerebral hemorrhage [ 7 ]. Mechanisms involved in cognitive decline are not yet fully clear but can be attributed to direct infection of the nervous system, the systemic hyper inflammatory response, acute respiratory distress syndrome (ARDS), invasive ventilation, and sedation or side effects of the drugs used for COVID-19 [ 52 ]. Figure 4 depicts the various possible routes of neuro-invasion of SARS-CoV-2.…”
Section: Pathogenesismentioning
confidence: 99%
“…As discussed earlier in the article, few studies have reported short-term memory loss and neurocognitive disorder following COVID-19 infection. Majorly proposed mechanism of neurodegeneration is chronic systemic inflammation [ 52 ]. A study established the correlation of inflammatory factors and levels of C-reactive protein (CRP) in the patients that exhibited cognitive dysfunction.…”
Section: Neurological Complications and Their Possible Mechanismsmentioning
confidence: 99%
“…Eine Analyse von über 40.000 COVID-19-Patienten zeigte neuropsychiatrische Manifestationen bei 22,5 % der COVID-19-Patienten [ 28 ]. Zu nennen sind vor allem Insomnien, Depressionen, Kopfschmerzen und Enzephalopathien [ 28 , 29 ]. Die potenziell irreversiblen kognitiven Defizite bei älteren Patienten nach durchgemachter COVID-19-Erkrankung sind annehmbar multifaktorieller Genese [ 29 ].…”
Section: Folgen Der Covid-19-pandemie Für äLtere Patienten Mit Kognitunclassified